Characterization of an air-based coaxial dielectric barrier discharge plasma source for biofilm eradication - Soler Arango, Juliana (2018)
Air-based atmospheric-pressure cold plasmas are a source of charged particles, excited species, radicals, and UV rays, known to induce degradation of biomaterials. In this work we characterize an air-based Dielectric Barrier Discharge plasma source designed for biofilm eradication, and study plasmas generated under different conditions by Optical Emission Spectroscopy. The main excited species in air-based plasmas are N2 (C3Πu) molecules and the gas temperatures never exceed 335 K, decreasing as air amounts increase in the feeding gas. Excited oxygen atoms and OH species are only detected in discharges generated in argon-containing gases. The temperature of the effluent remains below 308 K. Air-based plasmas are useful for biofilm eradication as they produce high amounts of ozone at a low gas temperature.